Research and Application of Inverter Over-current Fault Diagnosis Based on EOVW Index and C&RT Decision Tree - WANG Tonghui; ZHANG Huiyuan; XU Wei; JIANG Ping (Kongzhi Yu Xinxi Jishu)
To solve the problem on the reason of inverter over-current fault and the classification recognition during converter operation, it presented a system diagnosis scheme combining EOVW index and decision tree. Based on the signal characteristics of converter output voltage and current which extracted from wavelet analysis, it built a system of inverter over-current fault diagnosis model using C&RT decision tree data mining thinking and classification function, which can locate effectively the reason on the inverter over-current fault. Final output of the scheme is a set of intelligent identification system, which is convenient and fast, without manual interception, and can be further adjusted and optimized with the accumulation of data.